Ornament and Crime : Thoughts on Design and Materials - Loos, Adolf; Translated by Shaun Whiteside (UK Penguin Books, 2019)
Adolf Loos, the great Viennese pioneer of modern architecture, was a hater of the fake, the fussy and the lavishly decorated, and a lover of stripped down, clean simplicity. He was also a writer of effervescent, caustic wit, as shown in this selection of essays on all aspects of design and aesthetics, from cities to glassware, furniture to footwear, architectural training to why 'the lack of ornament is a sign of intellectual power'
Keywords: Europe -- Decorative arts -- Austria -- Decoration and ornament -- Loos, Adolf, 1870-1933